Carpal Tunnel Syndrome - ใจรักดี เยาวภา; เติมวรกุล ลดาวรรณ; เสถียรพันธฤทธิ์ ไพบูลย์ (Journal of Health Science of Thailand, 2021)
Carpal tunnel syndrome is caused by the thickening of the transverse carpal ligament (flexor retinaculum) located on the palmar side of wrist pushing or pressing on the median nerve. The major causes are repetitive work, heavy hand use, and prolonged use of tools with strong vibrations. The signs and symptoms are burning pain, numbness the palmar side of the hand, especially at the thumb, the index, the middle and radial side of the ring fingers. The symptoms mostly occur at night or during waking up. Management can be divided into 2 types: firstly, conservative interventions such as splint, medication, steroid injection, and physical therapy, secondly, surgical approaches. Appropriate management for each patient depends on individual severity and conditions.